Divergência genética entre acessos de mamoeiro e correlações entre suas características no norte do Espírito Santo - Silva, Clemilton Alves da (2013)
Papaya (Carica papaya L.) is currently one of the most economically important fruit crops being cultivated and consumed in tropical and subtropical regions of the world. Brazil is the second largest producer of the fruit, its cultivation is configured in highyield agriculture and great economic importance to the country. The improvement works in papaya crop are becoming important tools in order to maintain and increase production indices of papaya tree. In this context developed two distinct works for the following purposes: the first was evaluated, the degree of genetic variability among accessions fifty-nine papaya through agronomic characteristics. For both the genetic divergence was quantified by multivariate following: Mahalanobis distance, clustering techniques and optimization Tocher hierarchical method agglomerative average peer unweighted. There were significant differences for all traits, showing the existence of variability among accessions. The characteristics plant height, height of insertion of the first fruit greater thickness of fruit pulp, fruit diameter and length of fruit provided heritability of more than 80%, results may indicate that significant gains in simple selection process. There is genetic variability among accessions, and the American, STZ 03-209 Petiole short and Califlora the most divergent. The methods of Tocher and hierarchical partially agree on the formation of heterotic groups of accessions of papaya in northern Espírito Santo. The characteristics of fruit weight, fruit diameter and plant height were the most contribution to genetic diversity. The second study was aimed at obtaining estimates of phenotypic correlations between morphological and papaya fruits as well as analyze the relationship between these characteristics and its unfolding in direct and indirect effects of primary and secondary components on production by plants. The correlations were higher to genotypic. There was no significant correlation among traits and the main variable yield per plant. The primary components: number and weight of fruit almost entirely explain the variations in plant production. Smaller thickness of fruit pulp was the secondary component that showed higher direct and indirect effects on the primary variable fruit weight.